COMPARISON OF TOTAL BILIRUBIN LEVELS IN SERUM WITHOUT LIGHT EXPOSURE DELAYED FOR 1 HOUR AND 3 HOURS - yuniwarsiti, niluh; Naim, Rizman; Taib, Laras Puspita (Journal of Health, Technology and Science (JHTS), 2024)
The total bilirubin test is one of the laboratory tests to determine the function of the liver and bile ducts. Impaired liver function can be shown by hemolytic anemia, liver cirrhosis, hepatitis, and hepatitis carcinoma. This study aims to determine the comparison of total bilirubin levels in serum without light exposure that is delayed for 1 hour and 3 hours. The method in this study uses a quantitative approach with a type of experimental research of Cross sectional design. The types of data used are primary data and secondary data. The sampling technique uses the purposive sampling technique, with a sample number of 10 samples. The results showed that the average value of total bilirubin examination in serum (immediately checked) with an average result value of 0.514 mg/dL, while in serum it was delayed for 1 hour with an average result of 0.513 mg/dL and serum was delayed for 3 hours with an average value of 0.511 mg/dL and the result of the value (significance) > from alpha (0.05) or (sig > 0.05) then Ho was accepted and Ha was rejected which means There was no difference in the results of total bilirubin levels in serum without light exposure that was delayed by 1 hour and 3 hours.